The Description of the Extremophile Reticulonema bolivianum gen. et sp. nov. (Microcoleaceae, Cyanobacteria) and the Review of the Phylogenetic Status of the Genus Capilliphycus Based on the 16S rRNA Gene - Guilherme Scotta Hentschke; Claudia Hoepfner; Daniel Guzmán; Vitor M. Vasconcelos (Plants)
This article describes a new genus and species of cyanobacteria isolated from Laguna Pastos Grandes in the Bolivian Altiplano. This discovery marks the first described species of this phylum from this extreme environment. Additionally, the phylogenetic status of the genus Capilliphycus is reassessed. The analyses are based on 16S rRNA gene maximum likelihood and Bayesian phylogenies, identity (p-distance), morphology and habitat comparisons. The new genus is a Lyngbya-like type from a mat at the margin of a brackish–alkaline lake with borax. It is phylogenetically close to Dapis, Tenebriella and Okeania, but compared to these genera, the maximum 16S rRNA gene identity values reached only 90.9%, 91.1% and 92.5%, respectively. The genus Capilliphycus was found to be polyphyletic. The type species Capilliphycus salinus is clustered with C. guerandensis. However, “C. tropicalis” and “C. flaviceps” form a distinct clade, distant from the Capilliphycus type species. Between the two “Capilliphycus” clades, Sirenicapillaria and Limnoraphis are found.